The Effectiveness of Information Education Communication (IEC) on Knowledge and Practices Regarding Patient Safety Measure among Nursing Officers in Selected Hospital of Pune City - Divyank Kalal1 , Dipak Sethi2 , Ranjana Chavan3 , Sharadha Ramesh4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background & Objective: Patient safety is very important in the provision of quality care. Our aim wasto assess the Information Education Communication (IEC) on knowledge and practices regarding patientsafety measure among nursing officers.Methods: A Pre-Experimental one group pre-test post-test design was adopted involving 60 nursing officers.After obtaining informed consent nursing officers were allocated by using the Non-probability Conveniencesampling technique. IEC module was given to the nursing officers after the Pre-test was taken. An intervalof 7 days was given then post-test was obtained. Tool used in the study are Self-Structured Questionnaire onassessment of knowledge and practice.Results: The average change in the level of knowledge was significantly increase in post-test as comparedto pre-test. In pre-test 70% of nursing officers have average knowledge, 28.33% have poor knowledge and1.67% have good knowledge. The mean knowledge of the nursing officers was 6.37 and standard deviationswas 0.71. While in the post-test 78.33% of nursing officers have good post-test knowledge, 21.67% haveaverage knowledge and no nursing officers have poor knowledge. The mean knowledge of the nursingofficers was 11.7 and standard deviations 1.75.The change in the level of practice was also significantly increase in post-test as compared to pre-test. Inpre-test 60% of the nursing officers have average practice score, while 36.67% have poor practice and3.33% have good practice. The mean practice of the nursing officers was 6.35 and standard deviations was2.37 while in the post-test 53.33% of the nursing officers have good practice, 46.67% have average practiceand no nursing officers have poor practice. The mean practice of the nursing officers is 13.5 and standarddeviations from to 0.71.Conclusion: The findings of the study shows that there is highly significant difference between the score ofpre-test and post-test. Therefore, and null hypothesis (H0) is rejected and IEC module is effective.